Dragons : Shorter Fiction of Leung Ping Kwan - Leung, Ping-kwan, 1949-2013 (Hong Kong literature series., 2020)
Leung Ping-kwan brought as much talent and inspiration to the writing of his short stories as he did to his poems. 'I have drawn on magical realism to explore the absurdity of Hong Kong,' he wrote of the story 'See Mun and the Dragon' (1975) in which we find him using a simple, clipped style. The later story 'Drowned Souls' (2007) was written in a more symbolic, lyrical and complex manner, influenced by the style of the traditional Chinese tales of the supernatural. Although the two stories are separated by over 30 years, dragons play a prominent part in both. The dragon has always been a fascinating creature, a complex embodiment of the timeless soul of China and a symbol of the creative energy and transformative possibilities of the Tao. Both of these enchanting stories are anchored in the author's ideas of freedom and liberation.